A new species of Aedes Meigen subgenus Ochlerotatus Lynch Arribálzaga (Diptera: Culicidae) from the coastal wetlands of the desert in northern Chile: morphological and molecular identification - González, Christian R; Reyes, Carolina; Rada-Chaparro, Viviana; Saldarriaga-Córdoba, Mónica (Zootaxa, 2017)
Aedes (Ochlerotatus) sallumae González & Reyes n. sp. is described and validated using morphological characters of the adult male and female, male genitalia and immature stages, and its cytochrome oxidase unit 1 mitochondrial gene sequence (COI). Aedes (Och.) sallumae is morphologically close to Ae. (Och.) albifasciatus (Macquart). However, these species can be distinguished based on characters of the males and females, male genitalia and fourth-instar larvae. Aedes (Och.) sallumae was collected in the geographically isolated desert zone of northern Chile, the Atacama Desert. This isolation suggests allopatric speciation, with Ae. (Och.) sallumae divergent from its sister species Ae. (Och.) albifasciatus. Molecular characterization showed a difference of more than 8% between these species, supporting their recognition as different species.